2021
DOI: 10.1080/09540121.2021.1902935
|View full text |Cite
|
Sign up to set email alerts
|

Family Connections randomized controlled trial: assessing the feasibility and acceptability of an intervention with adolescents living with HIV and their caregivers in Ndola, Zambia

Abstract: Achieving the 95-95-95 UNAIDS targets requires meeting the needs of adolescents, however we lack evidenced-based approaches to improving adolescent adherence to antiretroviral therapy (ART), increasing viral suppression, and supporting general wellbeing. We developed Family Connections as a group intervention for adolescents and their adult caregivers and conducted a randomized controlled trial in Ndola, Zambia to test feasibility and acceptability. Fifty pairs (n = 100) of adolescents (15-19 years and on ART … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…The evidence review identified 70 intervention evaluations [29–98]. The literature flow is documented below (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence review identified 70 intervention evaluations [29–98]. The literature flow is documented below (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Denison et al pilot-tested the “Family Connections” family-based intervention among AYAs, ages 15 to 19 years, living with HIV in Zambia. Based on positive youth development, Family Connections moved beyond individual level factors to engage the family caregivers (interpersonal level) and health care providers (environmental level) [ 114 ]. To expand on this pilot study, the team is now conducting a National Institute for Mental Health—funded R01 to examine both the impact of Family Connections on youth achieving an undetectable viral load, and if developmental differences among participants (e.g., cognitive functioning, emotional regulation and impulse control) moderate any impact found.…”
Section: Discussionmentioning
confidence: 99%
“…38 Individual-, clinic-, and community-level interventions addressing these and other factors are emerging. [39][40][41] Rapid scale-up of interventions found to be effective will be needed to ensure efforts to end of the epidemic are not compromised. Our study also reinforces others that have documented a substantial decrease in time to ART initiation after launch of treat-all policies circa 2015 and a subsequent increase in viral suppression.…”
Section: Discussionmentioning
confidence: 99%